Development of Fixed Bed Reactor for Application in GTL-FPSO: The Effect of Nitrogen and Carbon dioxide Contents in Feed Gas on Fischer-Tropsch Synthesis Reaction over Ru/Co/Al2O3 Catalyst - Hong Gihoon; Moon, Dong Ju (ISAHOF, 2019)
The FTS reactions over Ru/Co/Al2O3 catalyst were performed in the shell and tube type fixed-bed reactor with an oil circulation system in order to investigate the effect of N2 and CO2 content. It was found that the N2 gas does not affect the product selectivity of the FTS reaction over Ru/Co/Al2O3 catalyst in the fixed-bed reactor at pilot scale but it has decreased the CO conversion. It was also found that the CO2 has affected the product selectivity of the FTS reaction through the chain growth reaction. It eventually has led the product distribution to shift to the short chain hydrocarbons in FTS reaction. As a result it is concluded that removing the impurities from the syngas in commercial GTL and GTL-FPSO plants is essential to enhance the economic efficiency of process.
Keywords: Co based catalyst; Fischer-Tropsch; Nitrogen Effect; Carbon Dioxide Effect; Ru/Co/Al2O3; GTL-FPSO